Does More Storage Give California More Water?. (23rd April 2019) - Nover, D.M.; Dogan, M.S.; Ragatz, R.; Booth, L.; Medellín‐Azuara, J.; Lund, J.R.; Viers, J.H.
Abstract: Increasing reservoir storage is commonly proposed to mitigate increasing water demand and provide drought reserves, especially in semiarid regions such as California. This paper examines the value of expanding surface reservoir capacity in California using hydroeconomic modeling for historical conditions, a future warm‐dry climate, and California's recently adopted policy to end groundwater overdraft. Results show expanding surface storage capacity rarely provides sizable economic value in most of California. On average, expanding facilities north of California's Delta provides some benefit in 92% of 82 years modeled under historical conditions and in 61% of years modeled in a warm‐dry climate. South of California's Delta, expanding storage capacity provides no benefits in 14% of years modeled under historical conditions and 99% of years modeled with a warm‐dry climate. Results vary across facilities between and within regions. The limited benefit of surface storage capacity expansion to statewide water supply should be considered in planning California's water infrastructure. Abstract : Research Impact Statement : Under baseline conditions, expanding storage provides benefits in some northern California locations. In a warm‐dry climate, benefits from expanding storage in southern California are negligible.